Tooth loss in the very old: 13–15-year incidence among elderly Iowans - Warren JJ, Watkins CA, Cowen HJ, Hand JS, Levy SM, Kuthy RA. (Blackwell Synergy, 2002)
Very few studies have reported tooth loss incidence over a period of 10 years or more, and fewer have reported tooth loss occurrence in subjects aged 80 and older, so that the long-term pattern of tooth loss in the very old is largely unknown.